Sustained reduction in the incidence of type 2 diabetes by lifestyle intervention: follow-up of the Finnish Diabetes Prevention Study - Lindström, Jaana; Ilanne-Parikka, Pirjo; Peltonen, Markku; Aunola, Sirkka; Eriksson, Johan G; Hemiö, Katri; Hämäläinen, Helena; Härkönen, Pirjo; Keinänen-Kiukaanniemi, Sirkka; Laakso, Mauri; Louheranta, Anne; Mannelin, Marjo; et al. (The Lancet (British edition), 2006)
Lifestyle interventions can prevent the deterioration of impaired glucose tolerance to manifest type 2 diabetes, at least as long as the intervention continues. In the extended follow-up of the Finnish Diabetes Prevention Study, we assessed the extent to which the originally-achieved lifestyle changes and risk reduction remain after discontinuation of active counselling. Overweight, middle-aged men (n=172) and women (n=350) with impaired glucose tolerance were randomly assigned to intensive lifestyle intervention or control group. After a median of 4 years of active intervention period, participants who were still free of diabetes were further followed up for a median of 3 years, with median total follow-up of 7 years. Diabetes incidence, bodyweight, physical activity, and dietary intakes of fat, saturated fat, and fibre were measured. During the total follow-up, the incidence of type 2 diabetes was 4·3 and 7·4 per 100 person-years in the intervention and control group, respectively (log-rank test p=0·0001), indicating 43% reduction in relative risk. The risk reduction was related to the success in achieving the intervention goals of weight loss, reduced intake of total and saturated fat and increased intake of dietary fibre, and increased physical activity. Beneficial lifestyle changes achieved by participants in the intervention group were maintained after the discontinuation of the intervention, and the corresponding incidence rates during the post-intervention follow-up were 4·6 and 7·2 (p=0·0401), indicating 36% reduction in relative risk. Lifestyle intervention in people at high risk for type 2 diabetes resulted in sustained lifestyle changes and a reduction in diabetes incidence, which remained after the individual lifestyle counselling was stopped.